Kaalaman at Kasanayan Sa Edukasyong Pantahanan at Pangkabuhayan (EPP) of Pre-Service Teachers in A State University: A Basis for Curriculum Enhancement - Yesha Marie Mayola Ferido; Janna Mae Elemento Ladringan; Ejie Buen Bernardino; Allysa Mae Gallardo Mayola; Irasha Mae Badar Fabros; Joseline Ragat Tamoria (Future Science / FSH-PH Publications, 2026)
A competent teacher demonstrates purpose in making teaching and learning meaningful. Edukasyong Pantahanan at Pangkabuhayan (EPP) requires mastery of both content knowledge and pedagogical skills across its five learning areas. Teacher expertise significantly influences instructional quality, often surpassing the impact of physical learning resources. In Technology and Livelihood Education (TLE), where theory meets hands-on application, both knowledge and skills are essential. Teachers must be well-prepared to demonstrate key concepts, model practical skills, and guide students toward meaningful, real-world learning experiences laying the foundation for future livelihood opportunities. The study used a mixed-method research design, specifically a sequential explanatory approach, to collect data in assessing the knowledge and skills competencies of pre-service teachers in EPP. The data was gathered from 20 Pre-service teachers at President Ramon Magsaysay State University – San Marcelino Campus through survey questionnaires and qualitative responses. Descriptive statistics was used to determine competency levels, while thematic analysis was applied to qualitative data. The findings revealed Pre-service teachers were proficient in Home Economics and ICT but developing in Agriculture, Industrial Arts, and Entrepreneurship. The challenges included limited access to tools and materials, insufficient hands-on learning opportunities, inadequate instructional resources, and time constraints affecting effective course implementation. To address these issues, the researchers recommend integrating curriculum enrichment strategies such as resource speakers who are experts in their respective fields, workshops, project-based learning, experiential and collaborative activities, and strengthened school-community partnerships. These enhancements aim to bridge competency gaps and better prepare Pre-service teachers for effective EPP instruction.